Weltaufgang: die Geburt des kosmologischen Denkens Eugen Finks: Eine Einführung in den dritten und vierten Teilband der »Phänomenologischen Werkstatt«-Ausgabe - van Kerckhoven, Guy; Giubilato, Giovanni Jan (Verlag Karl Alber, 2023)
The third and fourth volumes of the ‘Phenomenological Workshop’ disclose in detail the entire mass of notes, drafts for seminars and outlines for research manuscripts that Eugen Fink left behind as a unique phenomenological legacy. They are all part of his early work, written in the years 1933 to 1945. In fact, through extensive critical revision of the philosophical principles at the heart of Husserlian transcendental phenomenology, Eugen Fink advanced slowly but steadily towards a radical ontological and cosmological renewal of phenomenology in his early notes and various research manuscripts. This book documents this ontological and cosmological renewal of phenomenology during the years 1933–1945.